PHYSIOTHERAPEUTIC PERFORMANCE IN PALLIATIVE CARE: AN INTEGRATIVE REVIEW ON THE EXISTENCE OF PHYSIOTHERAPEUTIC PROTOCOLS FOR PALLIATIVE CARE - Lima, Antônio Víctor Silva; de Britto, Lidiane Régia Pereira Braga (Seven Editora, 2024)
Physiotherapy is a fundamental part of the multiprofessional team to promote quality of life and comfort to patients in palliative care, acting in the assessment, prevention and treatment of the dysfunctions presented, being essential to provide physical, emotional and functional comfort to patients. The present study is characterized as an integrative review guided by the following question: "In view of scientific publications, is it possible to establish a physical therapy protocol for palliative patients?". Thus, the objective of the study is to research the scientific productions about the physiotherapeutic techniques used in palliative care in the face of a multiprofessional work. An integrative literature review was performed in the PubMed (National Library of Medicine and National Institutes of Health), VHL (Virtual Health Library), PEDro (Physiotherapy Evidence Database) and SciELO (Scientific Electronic Library Online) databases, using the following descriptors: ("physiotherapy" AND "palliative care" AND "oncology" AND "neoplasm"). Including in the study only the journals 2017 to 2023 as publication date limits. Through the studies analyzed, it was observed that physical therapy acts actively in the face of the main complications reported by patients in palliative care, using techniques such as kinesiotherapy, aerobic exercises, resistance exercises, respiratory physical therapy techniques, neurofunctional physical therapy, TENS, therapeutic massage, compressive bandaging and myofascial release. It was possible to observe, through analyses and studies, that the intervention of physiotherapy plays a crucial role in palliative care, being considered an essential and complementary part within the multidisciplinary context of treatment. The physiotherapy approach in this scenario aims not only to relieve physical symptoms, such as pain and fatigue, but also to promote quality of life and emotional well-being for patients. However, when considering the development of specific protocols for certain conditions presented by patients in palliative care, we are faced with significant challenges, where the scarcity of well-founded studies in this area is notable, which makes the definition of evidence-based guidelines and practices a complex task. The diversity of cases and the individuality of each patient also contribute to the difficulty in establishing standardized protocols. DOI:https://doi.org/10.56238/sevened2024.037-031